Optimasi Pemisahan Perak dari Limbah Fixer melalui Variasi Tegangan - Efita Pratiwi Adi; Hartono Hartono; Zaroh Irayani; Adilla Luthfia; Adam Mulawarman (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
Fixer solution is a chemical substance in the form of a concentrated liquid that is used to wash radiographic films. The Fixer Solution functions to dissolve the silver halide layer on unexposed radiographic films. This research aims to design a waste fixer solution processing device using the electrolysis method and to regulate the voltage to the optimal point to produce a large electrolysis rate. Design an electrolysis device using stainless steel electrodes with a trapezoidal cathode with parallel sides of the cathode with lengths of 170 mm, 145 mm and a cathode height of 155 mm. The anode is rectangular with a length of 30 mm and a height of 169 mm. The method for making tools goes through several stages, namely making tool designs, testing tools, and testing waste fixer solution. The fixer waste used comes from Betesdha Wonosari Hospital. In this research, each test used 5 liters of fixer waste at each voltage which was regulated for 3 hours. The higher the mass voltage produced, the higher the electrolysis rate will be. However, the higher the voltage, the faster the sulfidation process will be. In the design of this fixer waste management tool, it can work optimally at a voltage of 4 V with a speed of 4.87 g/hour.